Stereochemical Definition of the Natural Product (6R, 10R, 13R, 14R, 16R, 17R, 19S, 20S, 21R, 24S, 25S, 28S, 30S, 32R, 33R, 34R, 36S, 37S, 39R)‐Azaspiracid‐3 by Total Synthesis and Comparative Analyses. Issue 3 (15th December 2017) - Kenton, Nathaniel T.; Adu‐Ampratwum, Daniel; Okumu, Antony A.; McCarron, Pearse; Kilcoyne, Jane; Rise, Frode; Wilkins, Alistair L.; Miles, Christopher O.; Forsyth, Craig J.
Abstract: The previously accepted structure of the marine toxin azaspiracid‐3 is revised based upon an original convergent and stereoselective total synthesis of the natural product. The development of a structural revision hypothesis, its testing, and corroboration are reported. Synthetic (6 R, 10 R, 13 R, 14 R, 16 R, 17 R, 19 S, 20 S, 21 R, 24 S, 25 S, 28 S, 30 S, 32 R, 33 R, 34 R, 36 S, 37 S, 39 R )‐azaspiracid‐3 chromatographically and spectroscopically matched naturally occurring azaspiracid‐3, whereas the previously assigned 20 R epimer did not. Abstract : A convergent and stereodefined total synthesis of the marine toxin azaspiracid‐3 (AZA3) enabled direct comparison with the natural product that redefines the structure of AZA3. Comparative data indicate that AZA1‐AZA10 and AZA34 share the (19 S*, 20 S* ) relative stereochemistry.